ELDERLY VISUAL TASK PERFORMANCE BY DIFFERENCES ON READING MEDIA AND LAMP POSITION IN A ROOM - Luciana Kristanto; Gunawan Tanuwidjaja; Joshua Antonio; Liana Maria Callista Lie; Marcellino Sebastian; Theresia Chany (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2018)
This research aimed to find out how lighting influence visual task performance of the elderly.The experiment was done on the table with different lamp position and by giving mark on the landolt ring chart printed on different reading media. Three position, the front, the middle and the back were the variables for lamp position, whilst different reading medias were the brown paper usually used for newspaper, the white silk uncoated paper or ‘HVS’ paper and the white gloss paper. The lamp were TL5 LED with 4000 °K and 6500 °K color temperature. The illumination level maintained specificly at 250-325 lux range. The respondents were 12 elderly with 58 years as the mean age. The result findings, for newspaper, the best position for speed was the front with 1.15 second per stroke; followed by the back with 1.18 second per stroke; and the middle got the lowest result with 1.4 second per stroke. For the HVS and glossy paper with higher luminance, the best for speed was the middle position that was the darkest in illumination, with 1.25 second per stroke for HVS and 1.3 second per stroke for glossy. The worst result was the back with 1.4 second per stroke for HVS and 1.36 second per stroke for glossy paper. For accuracy, the best for newspaper was the front, 96.02%. For the HVS paper, the middle and the back position has got the same highest accuracy, 90.45%. For the glossy paper, the middle position has got the highest accuracy, 91.62%. The visual task performance result, for the newspaper, the front position has got the highest score, followed by the back position that have brighter in illumination, but the score was lowest for the middle position. Contrary, for white HVS and white gloss paper, which get almost identic result, the middle position which was rather dark in illumination was the best, while the front and the back position were worse in visual task performance score. So that can be concluded that the higher illumination level was not always give the best to visual task performance; but depending to the user and the kind of paper or reading media as well.